Leptin, blood pressure, and left ventricular mass in obese adolescents - David Kaunang; Handri Widodo; Vivekenanda Pateda (Indonesian Pediatric Society Publishing House, 2013)
Background Obesity is characterized by an excessive accumulation of body fat and has become a major health problem in industrialized societies especially with regards to heart disease. Adipose tissue derived hormone (leptin) can cause obesity. Leptin acts to reduce food consumption and enhance energy expenditure. Objective To assess for a relationship between leptin, blood pressure, and left ventricular mass in obese adolescents. Methods This was a cross-sectional study conducted from November 2011 to April 2012 in Prof. Dr. RD. Kandou Hospital. This study included obese and healthy adolescents aged 13-18 years who attended school in Tuminting District ofManado. Each subject underwent measurements of body mass index (BMI), boold pressure, and plasma leptin level. Correlation regression test was used for data analysis. Results were considered to be statistically significant if P values < 0.05. Results There was a significant relationship between leptin and left ventricular mass (r=-0.467; P=0.006), as well as leptin and systolic blood pressure (r=-0.366; P=0.028), but not between leptin and diastolic blood pressure (r=-0.261; P=0.09). We also found significant relationships between systolic blood pressure and left ventricular mass (r=0.724; P<0.001), and between diastolic blood pressure and left ventricular mass ( r=0.615; P< 0.001) in obese adolescents. Conclusion Higher leptin levels are associated with lower left ventricular mass and lower systolic blood pressure, but are not associated with diastolic blood pressure.